EFFECTIVENESS OF APPLICATION OF FIRST HOUSE POLICY INTO PRACTICE - บุญเทพประทาน, ไวษิษฐ์ (RMUTT Global Business and Economics Review, 2016)
The research objectives consist of studying the problem and obstructed of the First Home Tax Rebate Policy context, studying on the impact factors of the First Home Tax Rebate Policy and finally developing effectiveness the First Home Tax Rebate Policy that be the most beneficial implementation. The research scope was conducted only in Bangkok. The significant interviewees included the public chief executives who are responsibility with the first home policy, three real estate associations and eights scholars. In this research, population and sampling unit were the consumers who participants with the First Home Tax Rebate Policy. In order to achieve the research objectives, both qualitative and quantitative researches were being implemented. While the qualitative research was used as the main study, the quantitative research was used to support the information validation. The researcher collects the qualitative research by purposive selection of eight depth interviewees from four groups of chief executives. The results were analyzed for finding on efficiency implementation. On the other hand, the quantitative research was collected the data from the consumers or the first home buyer on this program to find out the related factors or external factors such as demographic information factors, public policy factors, consumer behavior factors, real estate industrials competition factors and entrepreneur factors which impacted on the First Home Tax Policy efficiency implementation. The researcher has developed model “The effectiveness Model of First House Policy” by the study of the various factors, which associated with four factors by the order from most to least: 1) competitive factors in the real estate industry 2) entrepreneurs aspects 3) the government policy 4) the consumer’s choice which effected the policies on the First Home Tax Rebate Policy to be implemented. Therefore, the government needs to be extremely focused on setting and implementing the First Home Tax Rebate Policy which will help the people to have their own home. Consequently, the public quality of living could be improved. The implementation of this policy can stimulate the entire industry of real estate on economic. Nevertheless, this policy could generate the country economics and reflects sustainable growth in the future.